The Indonesian Ministry of Finance’s 2021 National Economic Recovery Program Strategy - Yuliana Yuliana (Administrative and Environmental Law Review, 2021)
The government has implemented the national economic recovery program in 2021. The Financial Ministry of Indonesia Republic has announced a press release based on the national economic recovery program. This program is essential because the COVID-19 pandemic has not been ended yet, although the vaccination program has been done. The economic recession still happens. This paper aims to describe the national economic recovery program in 2021. Methodology: a literature review. Literature was derived from Google Scholar and Science Direct.  The result showed that the National Economic Recovery Program coordinates and synergy among the Government, Bank Indonesia, Finance Service Authority, Saving Guarantee Institution, and banks. The national economic recovery program protects the consumption and purchasing power of the poor and vulnerable, funding for small and medium enterprises, tax incentives for businesses, the establishment of labour-intensive projects to absorb labour, and credit restructuring.